Outcomes of Pediatric Patients with Crohn’s Disease Received Infliximab or Exclusive Enteral Nutrition during Induction Remission - Yao Lv; Yue Lou; Gan Yang; Youyou Luo; Jingan Lou; Qi Cheng; Jindan Yu; Youhong Fang; Hong Zhao; Kerong Peng; Jie Chen (Gastroenterology Research and Practice)
Background. Both exclusive enteral nutrition (EEN) and infliximab (IFX) are recommended as induction therapy for pediatric Crohn’s disease (CD). Our aim was to compare long-term disease outcomes of patients initially received with either IFX or EEN. Methods. Medical records of newly diagnosed, therapy naïve pediatric patients with CD received with IFX or EEN as induction therapy were retrospectively enrolled. Pediatric Crohn’s disease activity index (PCDAI), Crohn’s disease endoscopic index of severity (CDEIS), and other clinical data were compared pre- and postinduction therapy in two groups. The sustained remission rates and time coupled with body mass index (BMI) and height for age (HFA) changes were evaluated during more than 2-year long-term follow-up. Results. We collected data from 58 children with CD used IFX (23) or EEN (35) as induction remission therapy from January 2015 through June 2021 in our single-center. The median follow-up after starting IFX or EEN was 12.2 months (6.5–18.0months) and 18.9 months (7.1–30.7months), respectively. The proportion clinical and endoscopic remission in EEN (88.57% and 68.75%) was similar with that of IFX (73.91% and 80.77%) after induction therapy. No significant differences were also observed in BMI and HFA recovery between two groups. Among those who achieved clinical or endoscopic remission or endoscopic response, the sustained remission rates and time did not reveal any significant differences for those 10 patients who used 6-mercaptopurine/methotrexate (6-MP/MTX) or 14 patients who used IFX as maintenance treatment during longitudinal follow-up. Conclusions. Our study suggested that EEN treatment is similar with IFX therapy in short-term outcomes, and EEN+6-MP/MTX treatment is comparable with IFX+IFX therapy in long-term outcomes.